PENGARUH KOMPETENSI SUMBER DAYA MANUSIA (SDM) DAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) terhadap KUALITAS LAPORAN KEUANGAN (KLK) - Lambok Vera Riama Pangaribuan Firmansyah Muhammad Danial (JURNAL RISET TERAPAN AKUNTANSI, 2017)
This study aimed to examine the effect of the application of The Influence of Human ResourcesCompetition and Region Financial Accounting System towards the Quality of Financial Statement in Palembang City. The population in this study is the Regional Working Units (on education) District.Fifty Cities. The sample of this study are 87 respondents that obtained from the head of the sub- section of finance, treasurer, and staf, but only 60 questionnaires can be processed. The data was collected by distributing questionnaires to the respondents directly concerned. Analysis technic of the data used is multiple linearregression with SPSS 20. The results showed: that the competency of HR positive significant effect on the quality of the financial reporting area. While the application of positive SAKD no significant effect on the quality of the financial reporting area.